2013
DOI: 10.1111/exd.12127
|View full text |Cite
|
Sign up to set email alerts
|

Cold atmospheric plasma, a new strategy to induce senescence in melanoma cells

Abstract: Over the past few years, the application of cold atmospheric plasma (CAP) in medicine has developed into an innovative field of research of rapidly growing importance. One promising new medical application of CAP is cancer treatment. Different studies revealed that CAP may potentially affect the cell cycle and cause cell apoptosis or necrosis in tumor cells dependent on the CAP device and doses. In this study, we used a novel hand-held and battery-operated CAP device utilizing the surface micro discharge (SMD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
169
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(178 citation statements)
references
References 30 publications
(31 reference statements)
8
169
1
Order By: Relevance
“…Cold atmospheric plasma can be used as a new strategy to induce senescence in melanoma cells [135]. Some researchers used a ‘miniFlat-Plaster’ that uses the flexible and scalable Surface Micro Discharge (SMD) technology for plasma production in air.…”
Section: Methods Of Productionmentioning
confidence: 99%
“…Cold atmospheric plasma can be used as a new strategy to induce senescence in melanoma cells [135]. Some researchers used a ‘miniFlat-Plaster’ that uses the flexible and scalable Surface Micro Discharge (SMD) technology for plasma production in air.…”
Section: Methods Of Productionmentioning
confidence: 99%
“…Previous studies have showed that the plasma irradiation is effective for melanoma therapy in vitro (12)(13)(14). To our knowledge, however, information about melanoma therapy by NEAPPs in vivo has not been presented.…”
Section: Introductionmentioning
confidence: 96%
“…These relatively short-lived RONS produced in media by plasma irradiation may be converted to other relatively long-lived species such as hydrogen peroxide (H 2 O 2 ), nitrate/nitrite (NO x ), and other uncertain species, which endow PAM with high and sustainable reactivity [13,16,17]. RONS are known to induce apoptosis via several signaling cascades including mitogen-activated protein kinase and phosphatidylinositol-3-kinase-Akt [8,18,19]. However, the mechanisms underlying the effects of PAM on cancer cells have not yet been elucidated in detail.…”
mentioning
confidence: 99%